Factor Analysis Of Purchasing Decisions Kopi Janji Jiwa In Bengkulu City (Factor Analysis of the Purchase Decision of Janji Jiwa Coffee in Bengkulu City) - Surya, Muhammad Hadi; Andriani, Evi; Fariadi, Herri (Universitas Dehasen Bengkulu, 2024)
Kopi Janji Jiwa, located in Bengkulu City, has become part of the coffee-loving community, with various menu variants offered, making more and more consumers come, the menu offered at Kopi Janji Jiwa is very diverse, starting from menus containing coffee, without coffee, earl gray series, soeram series, berry series, pandan series and the newest series, namely the milk tea series. The decision to purchase a product is the final action in the process of purchasing a product. Producers must understand what consumers actually expect from a product, so they can carry out appropriate marketing strategies to achieve sales goals. Several factors that influence consumers in making purchasing decisions include price, product, consumer tastes, location and promotion. This research aims to analyze purchasing decisions at Kopi Janji Jiwa, Bengkulu City and to analyze factors related to purchasing decisions for Kopi Janji Jiwa, Bengkulu City. Determining the research location was carried out purposively, using primary data and secondary data. The data analysis method used in this research is descriptive analysis which aims to answer the first objective of this research, namely the decision to purchase Janji Jiwa Coffee in Bengkulu City. To analyze factors related to purchasing decisions, non-parametric statistical analysis methods are used, namely the Spearman Rank correlation test. To find out whether there is a relationship between variable X and variable Y, a non-parametric statistical analysis tool is used, namely the Spearman Rank correlation test (Rs). The results of this research, namely answering the first problem formulation with the Purchase Decision Assessment, have a final score of 4.04, which means it is included in the good category. Factors related to the decision to purchase Janji Jiwa Coffee are product, price, place and promotion with the decision to purchase Janji Jiwa Coffee having a very significant relationship with a strong relationship with the decision to purchase Janji Jiwa Coffee in Bengkulu City.